Tantangan dan Prospek dalam Penyelesaian Sengketa Internasional: Sebuah Tinjauan Hukum Globalisasi - Saumi Triutami; Riyadi Solihin; Widi Wijayanti (Bulletin of Community Engagement, 2024)
The phenomenon of globalization introduces new complexities in international dispute resolution, expanding inter-state interactions but also presenting new challenges such as transnational crimes and environmental issues. This study aims to identify and analyze these challenges and seek effective solutions within the existing legal framework. The method used is descriptive analysis with a qualitative approach, focusing on literature review. The findings suggest that enhanced international cooperation and the strengthening of international law can help overcome challenges in international dispute resolution, promoting global peace and justice. The prospect of resolving international disputes using a global legal approach is very promising in the complex era of globalization. Strengthening diplomacy and negotiations, use of international dispute resolution mechanisms, and collaboration with non-state actors are important steps to achieve a just and peaceful resolution. Keywords: International Dispute Resolution, International Law, Globalization